Efficiency Evaluation of Two Media for In Vitro Maturation of Buffalo Oocytes - Patel, Parth S.; Suthar, Vishal S.; Suthar, Babulal N.; Patil, Deepak B.; Joshi, Chaitanya G. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study was conducted to evaluate morphometry of ovarian functional structures and effect of two different commercially available in vitro maturation (IVM) media on cytoplasmic and nuclear maturation of slaughter origin buffalo oocytes. The buffalo ovaries were collected from Ahmedabad Municipal slaughter-house, Ahmedabad and were transported at the laboratory within 2-3 h of slaughter at 33 to 35°C warm normal saline. The ovaries were washed and processed under laminar floor and evaluated for functional structures like mature corpus luteum (CL) and follicles i) <3 mm (small), ii) 3 to 6 mm (medium) and iii) 6 mm (large). The cumulus oocytes complexes (COCs) were aspirated with 18 G needle in 5 mL sterile disposable needle. The COCs were graded in to four categories (I to IV) and first three categories of COCs were used for IVM. For IVM 90 µL drops of BO IVM (IB; Bioscience) and IVM (VB; Vitrogen, Brazil) media were prepared and kept in benchtop incubator at 5 % O2, 5% CO2 and rest N2 at 38.5 °C. The selected COCs were randomly allocated to two media treatments and incubated for 22 h. The cytoplasmic and nuclear maturation were observed using morphology and nuclear staining method (Hoechst 334452). The weight of ovaries with CL (6.63 ± 0.18 g) was significantly higher as compared to without CL (4.33 ± 0.14 g). Total 546 visible follicles with average 2.15 per ovary observed were aspirated from 254 buffalo ovaries and 440 COCs were collected. Overall oocyte recovery per ovary (OR/O), follicle recovery per ovary (FR/O) and oocyte retrieval per follicle (OR/F) were 1.73, 2.15 and 0.81, respectively. The small, medium and large follicles were 43.04, 41.94 and 15.01 %, respectively. The mean ± SE (n) count of oocytes with Grade I, Grade II, Grade III and Grade IV were 6.90 ± 0.61 (138), 6.50 ± 0.48 (130), 4.35 ± 0.40 (87) and 4.25 ± 0.54 (85) with recovery rate of 31.36, 29.54, 19.77 and 19.31 %, respectively. Total 133 and 137 COCs were randomly allocated to IB and VB media treatment. Total cytoplasmic maturation in IB and VB was 79.69 and 73.71 %. Similarly, the nuclear maturation was 78.19 and 71.53 % in IB and VB media. No significant differences in cytoplasmic or nuclear maturation between two media were observed. The study concludes that CL influences ovarian weight and both commercial medias can be used for successful in vitro maturation of COCs of buffaloes.